RPTPα controls epithelial adherens junctions, linking E-cadherin engagement to c-Src-mediated phosphorylation of cortactin - Truffi, Marta; Dubreuil, Véronique; Liang, Xuan; Vacaresse, Nathalie; Nigon, Fabienne; Han, Siew Ping; Yap, Alpha S; Gomez, Guillermo A; Sap, Jan (Journal of cell science, 2014)
Epithelial junctions are fundamental determinants of tissue organization, subject to regulation by tyrosine phosphorylation. Homophilic binding of E-cadherin activates tyrosine kinases, such as Src, that control junctional integrity. Protein tyrosine phosphatases (PTPs) also contribute to cadherin-based adhesion and signaling, but little is known about their specific identity or functions at epithelial junctions. Here, we report that the receptor PTP RPTPα (human gene name PTPRA) is recruited to epithelial adherens junctions at the time of cell-cell contact, where it is in molecular proximity to E-cadherin. RPTPα is required for appropriate cadherin-dependent adhesion and for cyst architecture in three-dimensional culture. Loss of RPTPα impairs adherens junction integrity, as manifested by defective E-cadherin accumulation and peri-junctional F-actin density. These effects correlate with a role for RPTPα in cellular (c)-Src activation at sites of E-cadherin engagement. Mechanistically, RPTPα is required for appropriate tyrosine phosphorylation of cortactin, a major Src substrate and a cytoskeletal actin organizer. Expression of a phosphomimetic cortactin mutant in RPTPα-depleted cells partially rescues F-actin and E-cadherin accumulation at intercellular contacts. These findings indicate that RPTPα controls cadherin-mediated signaling by linking homophilic E-cadherin engagement to cortactin tyrosine phosphorylation through c-Src.